Función protectora en el modelo murino de la inmunoglobulina G equina antilipoproteína de 17 kDa de rhodhococcus equi - Fernández G., Ana S.; Lupidio M., María C.; Gómez L., Susana A.; Prescott, John F. (Avances en Ciencias Veterinarias, 1996)
R.equi es el agente productor de patologías más importante en el potrillo Pura Sangre de Carrera (PSC) de 0-6 meses de vida. Puede causar bronconeumonía crónica supurativa, enteritis ulcerativa y linfangitis mesentérica o superficial. Esta enfermedad tiene distribución mundial y produce una mortalidad de 322% en haras de potrillos de esta raza. El reservorio natural de R.equi es el suelo y la infección se adquiere por la inhalación o ingestión del alimento contaminado. No es sensible a los antibióticos convencionales y hasta el momento la única forma de profilaxis conocida es la administración parenteral de suero hiperinmune anti-R.equi obtenido en caballo adulto. Recientemente se ha identificado que las cepas virulentas expresan una lipoproteína de 17 kDa, que es inmunogénica y está codificada por un plásmido de 85-90 kb. Es nuestro propósito la producción de anticuerpos purificados contra esta lipoproteína de 17 kDa, para estudiar su rol en la defensa del potrillo hipogamaglobulinémico y así evaluar la posibilidad de administración parenteral en el huésped susceptible en haras enzoóticas. Palabras claves: Rhodococcus equi. Abstract Rhodococcus equi is the most important pathogen that affects in PSC foal (0-6 months of age) in Argentina. It causes pyogranulomatosa chronic pneumonia, ulcerative enteritis, and mesenteric or superficial, linphagitis and linphadenitis. This disease is widespread all over the world, but in Argentina it causes 3-22% morbility, with 87-92% mortality in Immunodeficient PSC foal. Distributed all over the country especially in the West of Buenos Aires Provincia, where the most important stud farms can be found. It is considered zoonosis specially in immunodeficient human and death, or fatal marker for any AIDS sick patient. R.equi is a soil organism, the foal acquires the infection by inhalation or ingestion of contaminated feed. Here Riequiisolation wasn't susceptible to conventional antibiotic, only sensitive to association Riphampicin-Ertritromicin or Gentamicin-Riphampicin, orally (with yogurt) and high dosis, parenteraly. Today the administration hyperimmune serum (1-2 litre all group of farm foals) against whole R.equi virulente, made from adult from healthy horse, is the only (hypothetic) way of control. Recently it has been established, that virulent Argentinian cultures show, a 15 - 17 - 19 kDa Lipoprotein, codified by a 85-90 kBa, very frail and termorregulated plasmid. Our purpose is produce purifield policlonal antibodies (IgG anti-lipoprotein 17 Kda) to be administered parenterally in susceptible host. For the study of role the Humoral Immunity in the colaboration and protection of the foal, and the use in minor dosis of the antibody, with better specific efficiency. For this reason, we tried it on 114 immunodeficiente Balb1c mice (using Indometacin as immunodepressor). Different concentration of equine IgG anti liprotein 17 kDa, was administered and challenged with dosis virulent R.equi. This mice serum was monitored for the IgG anti 17 -kDa levels by Elisa (17 kDa - ELISA), techniques of Immunohistochemistry and culture on infected mice lung, spleen, liver and feces. The results show protective dosis in the inmuno dificent Balb-c mice. At present we continue our job on the foal high endemic farm, with the use of the same and other dosis. Key words: Rhodococcus equi. R.equi, anti 17 kDa IgG. Foal.